Clinico-Pathological Features of Chronic Myelocytic Leukemia (CML) in Patients Presenting at A Tertiary Care Center - Hira Arooj, Hamida Qureshi, Asfandyar Shah Roghani, Khalid Khan, Saira Nasr Malik, Saliha Syed (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Chronic myelocytic leukemia (CML) is a slow growing disorder marked by excessive proliferation of cells of myeloid origin which do not lose their capacity to differentiate. Because of unavailability and un-affordability of such markers in most of our tertiary care centers, it is important to have a better understanding of clinical and hematological insight of this disease. Objective: To determine the clinical and hematological features of chronic myelocytic leukemia on bone marrow examination and trephine biopsy Material and method: The current study was cross-sectional study carried out at the Department of Hematology, Hayatabad medical complex, Peshawar from 8/4/2021 to 8/10/2021. In this study a total 196 patients were observed. The findings of bone marrow aspirate for morphology and phase of the disease, along with the trephine biopsy for bone marrow fibrosis were noted. All data with the demographic information like name, age, gender, occupation for further analysis were recorded. Results: In the current study, totally 196 patients were included. There were 112(57%) male patients and 84(43%) patients were female in our study. Based on clinical features and hematological features of patients with chronic myelocytic leukemia, 153(78%) patients had splenomegaly, 102(52%) patients had fever, 192(98%) patients had leukocytosis, 94(48%) patients had anemia. Conclusion: Our study concludes that the frequency of clinical and hematological features i.e. splenomegaly was 78%, fever was 52%, leukocytosis was 98%, anemia was 48% in patients presenting with chronic myelocytic leukemia. Keywords: clinical and hematological features, chronic myeloid leukemia.